Implementasi metode read aloud dalam mengembangkan kosa kata anak di kelompok A TK Mentari Loa Janan - Mariana, Annisa Dwi; Robingatin, Robingatin; Sunanik, Sunanik (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2024)
This research is motivated by the importance of developing children's vocabulary in their language skills. The choice of method for implementation is also no less important. It is hoped that choosing the read aloud method will provide a pleasant atmosphere and be able to facilitate children in acquiring vocabulary. This method is a means that can provide a wide variety of vocabulary to children. The aim of this research is to determine the implementation of the read aloud method in developing the vocabulary of children in group A. This research is field research with a qualitative approach. Data was collected through observation, interviews and documentation. The subjects in this research were the Principal and Teacher of Mentari Loa Janan Kindergarten. The validity of the data was tested through triangulation of sources, techniques and time. Data analysis refers to the work steps of Miles, Huberman, and Saldana involving data condensation, data presentation, and drawing conclusions. The results of this research relate to the implementation of the read aloud method applied by teachers in developing children's vocabulary. Planning consists of selecting books that suit the learning theme and pre-reading the books. The implementation consists of creating a pleasant atmosphere, showing and introducing the book cover, actively interacting with the children, asking questions to the children and discussing about 4-5 new vocabulary words in the book. Evaluation is carried out by asking children about the story they have just read, including the content, concepts and vocabulary. Assessment of vocabulary development itself is carried out by paying attention to children's conversations and language use. Although the research results provide an overview of the implementation of the read aloud method, further research is still needed to evaluate the long-term impact on children's vocabulary development. This can be a basis for developing more concrete recommendations to increase the effectiveness of using the read aloud method in the context of vocabulary development for children in group A.